Characteristics and outcomes of maternal cardiac arrest: A descriptive analysis of Get with the guidelines data. (November 2018) - Zelop, Carolyn M.; Einav, Sharon; Mhyre, Jill M.; Lipman, Steven S.; Arafeh, Julia; Shaw, Richard E.; Edelson, Dana P.; Jeejeebhoy, Farida M.; ,; Grossestreuer, Anne; Moskowitz, Ari; Edelson, Dana; et al.
Abstract: Background: Maternal mortality has risen in the United States in the twenty-first century, yet large cohort data of maternal cardiac arrest (MCA) are limited. Objective: We sought to describe contemporary characteristics and outcomes of in-hospital MCA. Methods: We queried the American Heart Association's Get with the Guidelines Resuscitation voluntary registry from 2000 to 2016 to identify cases of maternal cardiac arrest. All index cardiac arrests occurring in women aged 18–50 with a patient illness category designated as obstetric or location of arrest occurring in a delivery suite were included. Institutional review deemed that this research was exempt from ethical approval. Results: A total of 462 index events met criteria for MCA, with a mean age of 31 ± 7 years and a racial distribution of: 49.4% White, 35.3% Black and 15.3% Other/Unknown. While 32% had no pre-existing conditions or physiologic disorders, respiratory insufficiency (36.1%) and hypotension/hypoperfusion (33.3%) were the most common antecedent conditions. In most cases, the first documented pulseless rhythm was non-shockable; pulseless electrical activity (50.8%) or asystole (25.6%). Only 11.7% presented with a shockable rhythm; ventricular fibrillation (6.5%) or pulseless ventricular tachycardia (5.2%) while the initial pulseless rhythm was unknown in 11.9% of cases. Return of spontaneous circulation occurred in 73.6% but 68 (14.7%) had more than one arrest. The rate of survival to discharge was 40.7% overall; 37.3% with non-shockable rhythms, 33% with shockable rhythms and 64.3% with unknown presenting rhythms. Conclusions: Maternal survival at hospital discharge in this cohort was less than 50%, lower than rates reported in other epidemiological datasets. More research is required in maternal resuscitation science and translational medicine to continue to improve outcomes and understand maternal mortality.